Archaiczne i anachroniczne ukrainizmy w polszczyźnie - Piela, Agnieszka (Przegląd Wschodnioeuropejski, 2026)
The article aims primarily to characterize the chronologically marked Ukrainisms present in the Polish language. Its material base is the latest register of Ukrainisms drawn up in 2023 by Kraków linguist Adam Fałowski. The excerpted material shows the richness of historical linguistic forms, but it is difficult to determine a reliable number of the described borrowings because, among other things, only part of the examined vocabulary has remained semantically unchanged since its first attestation in Polish sources. The article focuses both on direct Ukrainian borrowings and words whose borrowing was mediated by the Ukrainian language (mainly orientalisms), for example, basałyk, bułat, czajka, horda, hreczkosiej, kociuba, kołczan, oczajdusza, szaławiła. The analysed words are an interesting linguistic document of life in distant ages. The realities of bygone days recorded in them reflect the centuries-old historical and cultural connections between Poland and Ukraine.